A Group Concept Inventing of Hiding. (January 2019) - Bunkers, Sandra Schmidt; Letcher, Deborah; Busman, Judy; Damgaard, Gloria; Flinn, Elizabeth; Knitig, Kathy; PetersonLund, Robin; Young, Linda
Parse's humanbecoming concept inventing model provided a unique method to conduct a group concept inventing of the humanuniverse living experience of hiding. Several insights related to conducting a group concept inventing project are identified along with an ingenuous proclamation for hiding.